2010
DOI: 10.3109/01902140903214683
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillation combined with arteriovenous extracorporeal lung assist reduces lung injury

Abstract: In order to optimize the lung-protective potential of high-frequency oscillatory ventilation (HFOV), it is currently recommended to maximize oscillatory frequencies. However, very high frequencies may lead to insufficient CO(2) elimination with severe respiratory acidosis. Arteriovenous extracorporeal lung assist (av-ECLA) allows near total CO(2) removal, thereby allowing for maximization of the lung-protective potential of HFOV. The aim of this study was to determine the impact of HFOV and av-ECLA on lung inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The remaining 16 animals had a mean weight of 54±4.3 kg. Fourteen of these animals, 7 per group, were also used in the companion paper [19]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 16 animals had a mean weight of 54±4.3 kg. Fourteen of these animals, 7 per group, were also used in the companion paper [19]. …”
Section: Resultsmentioning
confidence: 99%
“…21/06) on 11 July, 2006. To yield eight animals per group as in the companion paper [19], a total of 18 animals were studied because one animal per group was unsuitable for the liver analysis. Juvenile female Pietrain pigs negative for malignant hyperthermia were fasted with unlimited water access.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study also found that high frequency improved lung recruitment ( Muellenbach et al, 2008 ). HFOV with extracorporeal membrane oxygenation (ECMO) has been shown to attenuate lung inflammation in a saline lavage pig model compared to a pressure control strategy with a V T of 6 ml/kg ( Muellenbach et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%